HISTOLOGY AND CYTOGENETIC STUDY OF CHORIONIC VILLUS TISSUE IN FIRST TRIMESTER ABORTION - SHAHIN KAZI; SONALI VIDHALE; S. V. KOTWALIWALE (International Journal of Pharma and Bio Sciences, 2013)
Pregnancy loss is a very common entity observed in obstetric practice.Most commonly it occurs in first trimester abortions. In this study we are doing histological and cytogenetic analysis of chorion villus tissue in first trimester abortion. This will help us to know whether the pregnancy loss was due to chromosomal abnormality. All the selected cases were in the age group 19-40 years. Abnormal karyotype was found in 38% of the cases. Trisomy was predominated followed by polyploidy, monosomyX, structural anomalies and other abnormality. Regarding histology, the highest precision in categorizing abnormal abortion reached with trisomy and triploidy. It was seen that placental microscopic study alone was not enough to give a proper aeitological diagnosis in case of spontaneous abortion. In conclusion cytogenetic analysis is necessary for differentiating between choromosomally normal and abnormal abortion for further management of the patient.